Management and Improvement of Grazing in Waste Lands of the United Provinces - Joshi, K. D. (Indian Forester, 1946)
The management and improvement of grazing in the waste lands of these provinces is an integral part of post war planning, having been provided for in the proposed programme of post war reconstrucHon in the U.P., which includes a large-scale scheme of land management covering the whole Of the U.P. (excepting the hill patties of Kumaon). There seems little doubt that one condition essential to the success of any scheme of grazing regulation in semindari lands is the co-operation of the local population. For ihis reason it is envisaged that as far as improvement of grazing and fodder resources is concerned, only the simplest and least restrictive schemes of regulation are really suitable for initial application. More complicated schemes involving a greater degree of restriction are both difficult and unpopular from the point of view of the villagers and inevitably lead to evasions. Such research as has been done in improvement of grazing in this province clearly points to the primary necessily for periodic monsoon closures to afford annual and neremrial grasses an opportunity to recuperate and to sustain themselves. Biennial monsoon closures for three to four months (i.e., closing half the area in the rains on a two years cycle therefore appears to be the most suitable for initial introduction on an extensive scale. Partial closures in the rains are moreover more convenient from the point of view of villagers, since any restrictions on pasturage are felt least. Keenly at that time. The following detailed note on this subject by the Divisional Forest Officer, Afforestation Division, U.P. Summarizes the work undertaken in this province under this head.